2010
DOI: 10.1089/fpd.2009.0311
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ampicillin, Gentamicin, and Cefotaxime on the Release of Shiga Toxins from Shiga Toxin–ProducingEscherichia coliIsolated During a Diarrhea Episode in Faisalabad, Pakistan

Abstract: The Shiga toxin-producing Escherichia coli (STEC) is an emerging foodborne pathogen. The proportion of cases attributed to STEC in an episode of diarrhea in the Faisalabad region of Pakistan was investigated. In addition, as increase in Shiga toxin (Stx) release after exposure to various antimicrobial agents is widely reported, we also elucidated the in vitro effects of three commonly used antibiotics (ampicillin, gentamicin, and cefotaxime) on Stx release. Isolation and detection of STEC was done using enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…Moreover, in similar experiments, some antibiotics (e.g., rifaximin, gentamicin, cefotaxime, fosfomycin, and kanamycin) were found to decrease, rather than increase, the toxin production (43,44). The effects of some antibiotics were strongly dependent on their concentrations, causing either an increase or decrease in efficiency of Shiga toxin production (44)(45)(46). In this light, it is important to note that it was reported recently that STEC strain O104:H4, which caused a recent outbreak in Germany, did not release Shiga toxin in response to therapeutic concentrations of ciprofloxacin, meropenem, fosfomycin, and chloramphenicol (47).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Moreover, in similar experiments, some antibiotics (e.g., rifaximin, gentamicin, cefotaxime, fosfomycin, and kanamycin) were found to decrease, rather than increase, the toxin production (43,44). The effects of some antibiotics were strongly dependent on their concentrations, causing either an increase or decrease in efficiency of Shiga toxin production (44)(45)(46). In this light, it is important to note that it was reported recently that STEC strain O104:H4, which caused a recent outbreak in Germany, did not release Shiga toxin in response to therapeutic concentrations of ciprofloxacin, meropenem, fosfomycin, and chloramphenicol (47).…”
Section: Discussionmentioning
confidence: 78%
“…Although increased production of Shiga toxins has been demonstrated after antibiotic treatment of STEC strains cultured under laboratory conditions (reviewed in references 17, 20, 22, and 23), it is worth noting that the vast majority of such experiments were performed with the use of subinhibitory concentrations. For example, concentrations between 1/2 and 1/64 MIC were used to demonstrate enhanced stx gene expression and/or release of Shiga toxins following addition of norfloxacin, ciprofloxacin, ampicillin, levofloxacin, streptomycin, chloramphenicol, and erythromycin (42)(43)(44)(45)(46). Moreover, in similar experiments, some antibiotics (e.g., rifaximin, gentamicin, cefotaxime, fosfomycin, and kanamycin) were found to decrease, rather than increase, the toxin production (43,44).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other studies [17, 19] have shown that cefotaxime and meropenem [44] do not affect stx gene expression. By contrast, it was reported [17, 18] that ampicillin increased stx gene expression. However, the present study showed that cefotaxime had little inductive effect on stx 2 gene expression.…”
Section: Discussionmentioning
confidence: 77%
“…At least one study in vitro showed that gentamycin may safely reduce the release of shiga toxin (Stx) from Shiga toxin producing E. coli , but evidence is lacking to recommend the use of this antibiotic in most cases 17. If antibiotics must be given, an animal study suggests that macrolides, such as azithromycin, may also be a safer option 18.…”
Section: Rationalementioning
confidence: 99%